Optimized Ammonia Leaching and Energy-Efficient Stripping for Lithium and Cobalt Recovery from Spent LiCoO2 Cathodes - Aisulu Batkal; Kaster Kamunur; Lyazzat Mussapyrova; Bagdatgul Milikhat; Rashid Nadirov (Metals, 2025)
This study investigates the optimization of an ammonia-based leaching process for the recovery of lithium and cobalt from spent LiCoO2 cathodes, coupled with an energy-efficient ammonia stripping approach. Kinetic analysis revealed that both lithium and cobalt extraction follow pseudo-first-order kinetics, with activation energies of 76.54 kJ/mol and 97.22 kJ/mol, respectively, indicating a chemically controlled process. Optimal leaching conditions were established at 6 M NH3, 1.5 M (NH4)2CO3, liquid-to-solid ratio of 10:1, and 70 °C for 5 h, achieving 82.5% lithium and 96.1% cobalt recovery. The ammonia stripping process was optimized for energy efficiency, with operations at 95–98 °C providing the best balance between rapid NH3 removal and energy consumption. At 98 °C, energy demand was reduced to ~282 kJ/mol, a sevenfold improvement over lower temperature operations. A stepwise separation strategy was developed, involving selective lithium precipitation at pH 10.7–10.8, followed by controlled ammonia stripping to precipitate cobalt at pH 8.8–9.0. This integrated approach offers a promising alternative to conventional acid-based recycling methods, combining high metal recovery with improved energy efficiency and reagent recyclability.